Psychosocial Effects of COVID-19 in the Ecuadorian and Spanish Populations: A Cross-Cultural Study - Chocho-Orellana, Ángela Ximena; Samper-García, Paula; Malonda-Vidal, Elisabeth; Llorca-Mestre, Anna; Zarco-Alpuente, Alfredo; Mestre-Escrivá, Vicenta (Frontiers in Psychology, 2022)
The world's population is currently overcoming one of the worst pandemics, and the psychological and social effects of this are becoming more apparent. We will present an analysis of the psychosocial effects of COVID-19: first, a cross-sectional study in an Ecuadorian sample (n = 301) and second, a comparative study between two samples from the Ecuadorian and Spanish populations (n = 83 each one). Participants completed an online survey to (1) describe how they felt (depression, anxiety, and stress) before and after confinement; (2) analyze which emotional and behavioral variables predict depressive symptoms, anxiety, and stress perceived after the confinement; (3) carry out a comparative study in a sample of Ecuadorian and Spanish surveys. Results indicate, first, that Ecuadorians experience significantly more depressive symptoms, anxiety, and stress after confinement. Second, variables which predict depressive symptoms and anxiety are greater public prosocial tendency, less stress as a challenge, and greater stress as a threat, as well as an empathetic tendency that implies greater emotional regulation. Experienced stress after confinement was predicted by a greater public prosocial tendency, as well as an empathetic tendency. Finally, scores for depression, anxiety, and stress are higher after confinement in both countries. However, results reveal the similarity of the psychosocial effects that are being experienced, regardless of the country, and the differences in the variables that can help explain these effects. This can contribute to the constitution of intervention plans which aim to soften and alleviate the effects produced by a situation such as that experienced with COVID-19.